(untitled) (International Journal of Atharva, 2025)
This study investigates the customer satisfaction with e-banking services in Nepalese commercial banks. The study has employed descriptive and casual research design. The sampling technique for the study followed non-probabilistic sampling technique. Data were analyzed by using different statistical technique such as descriptive statistic, correlation analysis and regression analysis. This study found that majority of the respondents agreed that empathy, assurance and reliability of e-banking services quality factor highly affects the banking customer’s satisfaction and they believe that their satisfaction was also high. The correlation analysis reveals that reliability of e-banking services has positive and significant relationship with customer satisfaction and also correlation between responsiveness and customer satisfaction is significant positive. At the same time, there is significant positive association between assurance of e-banking services and the customer satisfaction. Likewise, tangibles and empathy have positive and significant relationship with customer satisfaction. Therefore, this study concluded that the impact of e-banking service quality on customer satisfaction is significant.